STRATEGI KOMUNIKASI YAYASAN UTAMA DALAM PENCEGAHAN HIV DAN AIDS PADA MASYARAKAT PEKANBARU - Danty Octavianty Roza; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
HIV ( Human Imunodeficiensi Virus) [is] virus cause of AIDS. There are in its body dilution [of] him like blood, sperma, or vagina dilution. Pengidap HIV will see healthy until HIV become AIDS during 5-10 year later;then. Although see healthyly [is] they earn catching with HIV [at] others. AIDS ( Aquired Immune Deficiency Syndrome) or downhill sindroma [it] impenetrability of caused [by] body [is] HIV so that body cannot fight disease. To depress case number of HIV and of AIDS this [is] needed [by] a[n way of prevention of its infection. One of [the] institute which care to prevention of HIV and of AIDS this [is] Especial Institution. Especial Institution [is] one of [the] LSM which care to health of society especially in case of HIV. this Especial Institution have stood since year 1993 and have vision that is the increasing of prosperity of life and health of society specially marginal society and rentan [in] province of Riau year 2025.Research use descriptive method qualitative pursuant to source of primary data and of sekunder and use technique data collecting of observation, documentation and interview, with determination of informan [pass/through] sampling of purposif counted ten one who compose five people of Especial institution that is Institution chief of Utama,Sekretaris and 3 people of staff Especial Institution [of] Pekanbaru and five people of outside party that is housewife, woman of tunasusila, cab driver, student and student. Technique analyse data use model analyse data of interaktif Miles and of Huberman by collecting obtained datas [is] later;then processed to be reduced, to be presented [is] so that yielded [by] a[n conclusion of public.Result of research indicate that [done/conducted] [by] communications strategy [is] Especial Institution [of] Pekanbaru in prevention of HIV and of AIDS [at] society of Pekanbaru for example Recognizing Especial Institution communications target in preventive program [of] HIV and of AIDS [at] society of Pekanbaru [is] woman of tunasusila, student, student, housewifes and worker, usage of Especial Institution media in preventive program [of] HIV and of AIDS [at] society of Pekanbaru, that is external media [of] room like banner and brochure and print in the form of book and also look in the face. Role of Especial Institution communicator in preventive program [of] HIV and of AIDS [at] society of Pekanbaru, becoming communicator [is] Especial Institution chief, health area head and of staff expert / technical. Communicator play a part in election of communications target, election of communications media and study of[is target of message of communications..Keywords : communications strategy, prevention of HIV and AIDS